Complex Approach to the Diagnosis of Children with Nasal and Nasopharyngeal Pathology. Key Results - Leyla S. Namazova-Baranova; Viktor A. Gankovsky; Irina V. Zelenkova; Svetlana G. Gubanova; Alexander V. Pashkov; George A. Karkashadze; Elena A. Vishneva; Elena V. Kaytukova; Kamilla E. Efendieva (Педиатрическая фармакология, 2023)
Background. Nasal and nasopharyngeal pathology is one of the most important and widespread challenge in pediatrics and pediatric otorhinolaryngology. Prolonged nasal breathing difficulty can be caused by various diseases and their combinations. It requires multidisciplinary approach to diagnosis with the involvement of modern examination methods and pathogenetic treatment. Objective. The aim of the study is to develop complex technology for the management of children with nasal and nasopharyngeal pathologies. Methods. The study included 240 children aged from 6 to 18 years. All patients were divided into 3 groups, comparable by sex and age: Group 1 – 85 patients with confirmed ENT-organ disease, Group 2 — 104 patients with confirmed allergic disease, control group — 51 somatically healthy patients who did not have any ENT-organ or allergic diseases. Examination procedures: diagnostic nasopharyngeal endoscopy, rhinomanometry (RMM), rhinoresistometry (RRM), olfactometry. Results. The obtained results (RRM, RMM) have shown that air flow rate in nasal cavity increased due to nasal resistance decrease. Nasal resistance was higher and air flow rate was lower in all children with various ENT-organs or allergic diseases compared to the control group. Nasal resistance decreased in all study groups (significantly in children with aggravation of allergic diseases of airways and ENT-organs diseases) as well as air flow rate increased in all study groups (significantly in Group 1 and 2) after anemisation of nasal mucosa with decongestants. Apparently, it can be associated not only with anatomical features (nasal septum deviation), but also with inflammatory features of nasal cavity and nasopharynx (adenoid hypertrophy and inflammation, persistent swelling of nasal mucosa at allergic rhinitis). We would like to present the algorithm for diagnosis of children with nasal and nasopharyngeal pathologies according to the study results. The following practical guidelines have been proposed: 1) all patients with complaints on prolonged nasal breathing difficulties require not only otorhinolaryngologist examination, but also diagnostic endoscopy of nasal cavity and nasopharynx; 2) in case of nasal septum deviation and complaints on prolonged nasal breathing difficulties, it is necessary to perform functional methods for nasal breathing evaluating (RRM, RMM) to choose adequate treatment method; 3) the use of RRM, RMM would help to choose the optimal treatment approach in children with complaints on prolonged nasal breathing difficulties and confirmed diagnosis of allergic disease (allergic rhinitis, hay fever, etc.), also associated with adenoid hypertrophy and/or nasal cavity and nasopharynx inflammatory diseases; 4) all patients with confirmed chronic diseases of ENT-organs should be examined by allergist, and, if necessary, should undergo comprehensive allergological examination. Conclusion. The developed complex approach to the management of children with nasal cavity and nasopharynx pathology is innovative and represents the technology of personalized use of modern, objective methods for diagnosing the nasal cavity and nasopharynx state. The presented diagnostic algorithm and practical guidelines allow us to establish diagnosis and choose the treatment tactics within a short time. The use of these studies in clinical practice will allow to monitor the therapy efficacy (including various pharmacotherapeutic strategies) for nasal cavity and nasopharynx diseases in children. Timely examination and pathogenetic treatment will allow to prevent the chronization of pathological process in ENT-organs. This is especially crucial in childhood as it provides children with the best chance of healthy growth and development.